The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1007/s00441-013-1574-1
|View full text |Cite
|
Sign up to set email alerts
|

Tenogenic differentiation of equine adipose-tissue-derived stem cells under the influence of tensile strain, growth differentiation factors and various oxygen tensions

Abstract: Mesenchymal stem cells have become extremely interesting for regenerative medicine and tissue engineering in the horse. Stem cell therapy has been proven to be a powerful and successful instrument, in particular for the healing of tendon lesions. We pre-differentiated equine adipose-tissue-derived stem cells (ASCs) in a collagen I gel scaffold by applying tensile strain, growth differentiation factors (GDFs) and various oxygen tensions in order to determine the optimal conditions for in vitro differentiation t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 49 publications
2
39
0
1
Order By: Relevance
“…On one hand, ASCs isolated from a variety of animal species have been reported to upregulate tenogenic markers in vitro under specific treatment, 13,14,18,20,51 suggesting the tenogenic potential of ASCs. On the other hand, Eagan et al questioned the suitability of hASCs for tendon tissue engineering and reported the lack of any significant and consistent upregulation in the expression of COL I, TNC, or SCX, in hASCs treated for up to 4 weeks with TGF-b1 or IGF-1.…”
Section: Discussionmentioning
confidence: 99%
“…On one hand, ASCs isolated from a variety of animal species have been reported to upregulate tenogenic markers in vitro under specific treatment, 13,14,18,20,51 suggesting the tenogenic potential of ASCs. On the other hand, Eagan et al questioned the suitability of hASCs for tendon tissue engineering and reported the lack of any significant and consistent upregulation in the expression of COL I, TNC, or SCX, in hASCs treated for up to 4 weeks with TGF-b1 or IGF-1.…”
Section: Discussionmentioning
confidence: 99%
“…Only limited cross-reactivity of monoclonal antibodies between species has been demonstrated in an earlier study [Ibrahim et al, 2007], in which only 14 of 379 monoclonal antibodies against human CD molecules showed cross-reactivity with equine leukocytes. Different techniques such as gene transfection [Wang et al, 2005a], gene transduction [Murray et al, 2010] and application of tensile strain, GDFs and oxygen tension [Raabe et al, 2013] have been attempted for the induction of tenogenic differentiation in MCSs. We evaluated the effect of exogenous supplementation of BMP-12 on tenogenic differentiation of equine AF-MSCs and observed that equine AF-MSCs could be differentiated into tenocytes by day 14 following supplementation of BMP-12 (50 ng/ml) to the growth medium, similar to observations by Violini et al [2009] for equine bone marrow, while 10 ng/ml BMP-12 supplementation in- which regulates the assembly of collagen fibrils and acquisition of biomechanical properties during tendon development [Zhang et al, 2006].…”
Section: Discussionmentioning
confidence: 99%
“…At first, there was the belief that tissue repair was obtained through the in vivo differentiation of the MSCs implanted to the prevailing cellular type in the tissue, i.e., when the MSCs were implanted in the tendon they would become cells similar to the tenocytes, thus favoring the synthesis of extracellular matrix (ECM) components and establishing the tissue repair. However, so far, it is known that the MSCs have tenogenic differentiation potential in vitro (RAABE et al, 2013). Evidences that the implanted MSCs may differentiate from the tendon cells in vivo still lack (CARVALHO et al, 2014b).…”
Section: The Action Mechanism Of Mscsmentioning
confidence: 99%
“…The adipose tissue is another important source, which stands out in equine tendinitis therapy (MUTTINI et al, 2012;REED;LEAHY, 2013). Recent studies show the tenogenic differentiation potential of mesenchymal stem cells from adipose tissue (AdMSCs), and they evidence the therapeutic potential of this source for equine tendinitis treatment (RAABE et al, 2013).…”
Section: Introductionmentioning
confidence: 99%